Features of psychological education in Ukraine during the war and post-war recovery - Koval, Vladyslav; Burlakova, Iryna; Sheviakov, Oleksiy; Kondes, Tetiana; Кондес, Тетяна Василівна; Кондес, Тетяна (Scientific Center of Innovative Researches OÜ, 2024)
The ongoing war in Ukraine and the ensuing post-war recovery have significantly transformed the nation’s educational and mental health systems. Psychological education has emerged as a vital field, addressing the escalating demand for mental health support, trauma recovery, and resilience-building among affected populations. This article explores the transformative adaptations of psychological education in Ukraine, including the integration of trauma-informed practices, the use of advanced therapeutic methods, and international collaborations. These efforts aim to equip professionals with the necessary skills to foster individual and societal healing in the face of adversity. This study aims to examine the distinctive features and adaptations of psychological education in Ukraine during the war and the post-war recovery period. Specifically, it seeks to identify strategies employed to address widespread trauma, enhance resilience, and promote societal healing. The article also highlights the role of trauma-informed education, community-based mental health initiatives, and global partnerships in shaping these educational transformations. The study employs a qualitative review methodology, synthesizing data from academic literature, institutional reports, and global frameworks on psychological education and mental health strategies. The analysis reveals several key features of psychological education in Ukraine during the war and post-war recovery: crisis-oriented curricula; practical training; remote learning and digital tools; resilience and coping mechanisms; cultural sensitivity and contextual adaptation; global collaborations. The article underscores the need for ongoing research to refine trauma-informed education and evaluate its long-term impact on both students and educators. Psychological education in Ukraine has undergone significant transformation, addressing the multifaceted challenges posed by war and recovery. By integrating advanced therapeutic practices, fostering community resilience, and leveraging global collaborations, Ukraine has established a robust framework for addressing mental health needs in conflict-affected regions. These efforts not only aid immediate recovery but also lay the foundation for a resilient and psychologically aware society.
Keywords: psychological education; trauma-informed practices; mental health; resilience; post-war recovery; Ukraine; global collaboration